Corporate finance : theory and practice - Quiry, Pascal; Vernimmen, Pierre (Chicester, West Sussex, U.K. : Wiley, 2011)
'The book, the website www.vernimmen.com and the Vernimmen.com newsletter are all written and created by an author team who are both investment bankers/corporate financiers and academics. This book covers the theory and practice of Corporate Finance from a truly European perspective. It shows how to use financial theory to solve practical problems and is written for students of corporate finance and financial analysis and practising corporate financiers. Corporate Finance: Theory and European Practice, 3rd Edition is split into four sections covering the basics of financial analysis; the basic theories behind valuing a firm; the major types of financial securities (equity, debt & options) and, finally, financial management; how to organise a company's equity capital, buying and selling companies, M&A, bankruptcy and cash flow management.Key features include: A section on financial analysis - a Corporate Financier must understand a company based on a detailed analysis of its accounts. Large numbers neglected this approach during the last stock market bubble and were caught in the crash that inevitably followed. How many investors took the trouble to read Enron's annual report? Those who did found that it spoke volumes! End of Chapter Summary, Questions and Answers, Glossary, European Case Studies A supporting Website http://www.vernimmen.com with free access to statistics, a glossary & lexicon; articles, notes on financial transactions, basic financial figures for more than 10,000 European and US listed companies, thesis topics, a bibliography; case studies, Q&A; A letter box for your questions to the authors - a reply guaranteed within 72 hours A free monthly newsletter on Corporate Finance sent out to subscribers to the site'--
'This book covers the theory and practice of Corporate Finance from a truly European perspective. It shows how to use financial theory to solve practical problems and is written for students of'--
Rev. ed. of: Corporate finance : theory and practice / Pierre Vernimmen. 2005.
Keywords: Corporations -- Finance; Business enterprises -- Finance